2019
DOI: 10.1007/s11423-019-09702-2
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of digital game-based technology on English language learning

Abstract: Learning with games has been increasing in practice, but review studies of the features and learning outcomes involving digital games to develop language learning are scarce. This scoping review investigates the current practices of digital game-based language learning to support English language learning, in terms of participants' characteristics, methodological features, gaming characteristics, and an association between game availability and gaming characteristics.Our results indicate: (1) vocabulary is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 78 publications
4
51
0
2
Order By: Relevance
“…The figure shows the large gap in game element quantity between games constructed for education versus entertainment. These findings are similar to those of Xu [27] in that the DGBLL applications are inconsistent in their quantity of game characteristics. Interestingly, bespoke games and games for education categories were similar in element quantity.…”
Section: What Are the Differences In Game Elements Between Bespoke Games Off-the-shelf Games Games For Education And Games For Entertainmsupporting
confidence: 86%
See 1 more Smart Citation
“…The figure shows the large gap in game element quantity between games constructed for education versus entertainment. These findings are similar to those of Xu [27] in that the DGBLL applications are inconsistent in their quantity of game characteristics. Interestingly, bespoke games and games for education categories were similar in element quantity.…”
Section: What Are the Differences In Game Elements Between Bespoke Games Off-the-shelf Games Games For Education And Games For Entertainmsupporting
confidence: 86%
“…A more recent review by Xu [27] filtered through results to analyze 59 research papers where English was the target language and examined DGBLL design. Xu found that vocabulary was the most prevalent language skill studied, and gameful elements lacked consistency amongst the digital games used.…”
Section: Previous Researchmentioning
confidence: 99%
“…At the same time, digitalization is considered as a different perception of pedagogical activity, when a teacher becomes a tutor, mentor, coach, coordinator, only directs and helps in development, and is not a translator of knowledge. This can be a way out into virtual reality with game pedagogical technologies as a condition for developing skills and applying them in problem situations [8]. Finally, digitalization is perceived as a different perception of graduates' competencies for the digital economy, which are subject to digital literacy requirements.…”
Section: Literature Analysismentioning
confidence: 99%
“…The benefits on the use of Information and Communication Technologies (ICTs) in the educational field are the personalization of the learning process (LIM; NEWBY, 2020), flexibility of time and space (WU et al, 2020;XU et al, 2020), communication (BARDAKCI et al, 2018;ZHAO;HUANG, 2020), active role of students (SALAS-RUEDA et al, 2020;SCHWARZENBERG et al, 2020) and development of skills (AL-SAMARRAIE et al, 2020;LIU et al, 2020).…”
Section: Introductionmentioning
confidence: 99%